2008
DOI: 10.1016/j.cretres.2008.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon deposition and phosphorus accumulation during Oceanic Anoxic Event 2 in Tarfaya, Morocco

Abstract: a b s t r a c tWith a multi-proxy approach, an attempt was made to constrain productivity and bottom-water redox conditions and their effects on the phosphorus accumulation rate at the Mohammed Plage section on the Tarfaya coast, Morocco, during the Cenomanian-Turonian Anoxic Event (OAE 2). A distinct d 13 C org isotope excursion of þ2.5& occurs close to the top of the section. The unusually abrupt shift of the isotope excursion and disappearance of several planktonic foraminiferal species (e.g. Rotalipora cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 65 publications
5
39
0
2
Order By: Relevance
“…In general, P is released as PO 4 3 − from decaying organic matter during oxic, suboxic and anoxic bacterial degradation below the sediment-water interface . However, under anoxic conditions, P is not retained in the sediment and generally diffuses upward from the sediment and returns to the water column (Mort et al 2008). Phosphorus enrichment may result from high OM supply in highly productive marine environments such as upwelling areas.…”
Section: Palaeoenvironmental Geochemical Proxiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, P is released as PO 4 3 − from decaying organic matter during oxic, suboxic and anoxic bacterial degradation below the sediment-water interface . However, under anoxic conditions, P is not retained in the sediment and generally diffuses upward from the sediment and returns to the water column (Mort et al 2008). Phosphorus enrichment may result from high OM supply in highly productive marine environments such as upwelling areas.…”
Section: Palaeoenvironmental Geochemical Proxiesmentioning
confidence: 98%
“…The degree to which remineralized organic P is retained as a reactive fraction in sediments depends on the redox conditions of the depositional system. In environments with at least intermittently oxic bottom waters, redox cycling of Fe in the sediments limits the diffusive flux of demineralized P to the overlying water column Mort et al 2008).…”
Section: Palaeoenvironmental Geochemical Proxiesmentioning
confidence: 99%
“…The total thickness of these three members was 72.56 m. Fortunately, a water well (drilling began in the lower section) nearby PM1 revealed 18 m of black shale with sustained thickness and developed pyrite, which was a positive signal of un-weathered Xinkailing-formation shale. This suggested that Xinkailing formation shale developed in a deep-water shelf with a strong anoxic environment, which is favorable for the preservation of organic matter [25,26]. The lithology of the Xinkailing formation was mainly comprised of black mud shale and carbonaceous shale.…”
Section: Shale-distribution Characteristicsmentioning
confidence: 99%
“…Mohammed Plage), Mid-Cenomanian-Early Turonian distal to proximal basin strata have been subdivided into various different microfacies and their palaeoenvironmental evolution has been described (El Albani et al 1999a). Different geo-, chemo-and biostratigraphical proxies have been studied for this anoxic period across the C/T boundary, which correlate these Tarfaya Basin sections among themselves and with other successions from the proto-North Atlantic and Tethys Oceans (Kuhnt et al 1990(Kuhnt et al , 1997Holbourn et al 1999;Kolonic et al 2002;Kuypers et al 2002;Tsikos et al 2004;Jenkyns et al 2007;Keller et al 2008;Mort et al 2008;Tantawy 2008). The Tarfaya Basin cyclicity has been interpreted as being forced by the Milankovitch precession (20 ka) and obliquity (39 ka) signals (Kuhnt et al 1997(Kuhnt et al , 2005), but short eccentricity (100 ka) origins (Kolonic et al 2005;Kuhnt et al 2009) for some of the observed cycles has also been proposed (each cycle representing a couplet of carbonate-rich and organic carbon-rich beds).…”
mentioning
confidence: 99%